2023
DOI: 10.1080/21645515.2023.2237374
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in vaccine coverage and confidence: A cause for concern

Abstract: Declining trends in vaccine confidence come at a time when routine immunization coverage for children has slumped to a decades-long low. With some of the largest losses in confidence experienced among young adults, this is a concerning trend with the potential for long-term implications. This article reflects on recent research examining the levels and trends of vaccine confidence over time and across the globe, the drivers influencing confidence, and the role of the COVID-19 pandemic in shaping confidence tod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…However, many countries have witnessed a decline in vaccine confidence. 33 This emphasizes need for continued efforts to uphold institutional trust and prevent a rise in vaccine hesitancy. Adequately addressing parental concerns and providing transparent, evidence-based information is likely to play an important role in building and maintaining this trust.…”
Section: Discussionmentioning
confidence: 99%
“…However, many countries have witnessed a decline in vaccine confidence. 33 This emphasizes need for continued efforts to uphold institutional trust and prevent a rise in vaccine hesitancy. Adequately addressing parental concerns and providing transparent, evidence-based information is likely to play an important role in building and maintaining this trust.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and polls in the U.S. and Canada have not shown significant changes in childhood vaccine hesitancy since the start of the COVID-19 pandemic [ 36 , 40 , 46 , 47 ]. On the other hand, global survey data demonstrated a decrease in the perception of the importance of vaccines for children in many countries before and after the start of the pandemic [ 48 , 49 ]. Further data are needed to fully understand the relationship between post-pandemic decreases in measles and rubella vaccination and changes in vaccine hesitancy.…”
Section: History and Current State Of Measles And Rubella Vaccine Hes...mentioning
confidence: 99%
“…Moreover, skepticism about the safety, efficacy, and necessity of vaccines, as well as concerns about their side effects, contributed to the decline in vaccination coverage, with the extent and magnitude of the problem increasing further during the epidemic[ 20 ]. Another study demonstrated that vaccination confidence is lost mainly among young people, which is a worrying trend that may have long-term public health consequences[ 22 ]. Furthermore, Kraaijeveld et al [ 23 ] pointed out that healthy children’s routine vaccination against COVID-19 was ethically unjustified.…”
Section: Routine Pediatric Vaccination During the Covid-19 Pandemicmentioning
confidence: 99%